A meal to ameliorate the Anthropocene - Brothers, Soren; McCarthy, Francine (Frontiers in Ecology and Evolution, 2024)
Despite (or perhaps because of) the staggering scale and pace of global change, the concept of the Anthropocene eludes discrete classification. There is widespread consensus that conditions associated with the Anthropocene, including rapid biodiversity loss and climate change, must be addressed if we are to enjoy ongoing and rich experiences. At the crux of human impacts is urban living – as of 2024 nearly 60% of people live in cities. Human societies are tightly interconnected with each other and surrounding ecosystems, but for city-dwellers, these connections may seem abstract. A failure to appreciate and foster such connections can have human and environmental health repercussions. We present a concept for a meal featuring local wild foods that could only be appropriately served under regionally ameliorated Anthropocene conditions. By presenting this hypothetical “solution”, we seek a common ground that spans human (and non-human) cultures and behaviors, and a concept that can be extended to any community. The simplicity of the “Anthropocene meal” belies three primary challenges: improvements to urban design, maintenance of ecosystem health, and shifting cultural attitudes. However, these barriers are quantifiable and may be addressed within annual to decadal timelines, making the Anthropocene meal a broadly achievable goal, and thus a valid source of optimism in a time of great uncertainty.